Overview of the 2003 workshop on detection and localization of marine mammals using passive acoustics - Desharnais, Francine; Hay, Alex E. (Canadian Acoustics, 2004)
The 2003 workshop on detection of localization of marine mammals using passive acoustics, held in Dartmouth, NS, Canada is discussed. The objective of the workshop is to provide a forum to the interested parties that can compare their detection and localization algorithms. A common dataset is provided to the participants by DRCD Atlantic and Dalhousie University. It is found difficult with marine mammals to establish the true number of properly identified vocalizations. The participants also exchanged views on automation and on collaboration opportunities, including sharing of algorithms, data and equipments.